A MIGHTEE Investigation of radio quiet AGN - Namane, Neo (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This study is aimed at being an overview and investigation of the behaviour and morphology of radio quiet (RQ) active galactic nuclei (AGN) in the radio and optical/near-infrared (NIR) bands. It is hoped that a concise description of the relation that exists between accretion activity and star formation (SF) will be achieved through utilization of multiwavelength astronomy analysis. This analysis includes the processing of data acquired from the MeerKAT International GHz Tiered Extragalactic Exploration survey (MIGHTEE), the Southern African Large Telescope (SALT), the Hyper Suprime Camera (HSC) mounted on the Subaru telescope and the VISTA telescope. In this thesis, several targets were observed using SALT spectroscopy, but a redshift of only one of them was obtained. Lastly, it was established that for the sample of RQ AGN studied, the AGN contribute a large fraction of the radio emission observed.
Keywords: Active galactic nuclei; Radio quiet zone; MeerKAT; Near infrared; Stars Formation; Southern African Large Telescope (South Africa : Telescope); VISTA